(untitled) (Ameghiniana, 2013)
The paper concerns with the study of a small freshwater ostracode fauna from the lower member of the Huantrai-co Formation in their type area, Huantrai-co, Neuquen province, Argentina, of Upper Cretaceous age (Lower Maastrichtian). The described and figured ostracods belong to the genera Ilyocypris, Candona? and Wolburgia?, representd by Wolburgia? neocretacea sp. n. This genus is mentioned for the first time for strata younger in age than Purbeck-Wealden.